MUET English examination as a predictor of academic achievement for TESL teacher trainees at a public teacher education institution in Malaysia - Baharum, Nurul Najwa; Abd Kadir, Nur Azliyana; Mohd Farid, Siti Nur Naquiah; Mohammad Shuhaimi, Nur ‘Izzah; Abdul Rahim, Wajihah; Razali, Abu Bakar; Abd Samad, Arshad (Human Resource Management Academic Research Society, 2021)
The Malaysian University English Test (MUET) is a standardised university entrance English language proficiency examination in Malaysia and is seen as one of the most important English language proficiency tests used by Malaysian public universities. Due to more international students (who have taken more internationally recognized English language proficiency tests) coming into Malaysian universities, it is important to assess the accuracy of the MUET as a benchmark to indicate the level of English proficiency of Malaysian students being at par with other international English assessment. In this regard, this study is conducted on a group of second year teacher trainees in the B. Ed Teaching English as a Second Language (TESL) program at a public university in Malaysia. A Bivariate Correlation Pearson test was conducted for the overall MUET score together with their CGPA (Cumulative Grade Point Average) to identify important predictors of academic achievement. The study found that the overall MUET scores and CGPA has positive correlation, and that MUET can serve as a predictive of academic achievement. Moreover, from the four components of MUET, only ‘Reading’ and ‘Speaking’ components seemed to be the heaviest predictors of students' academic achievement.